Analytical simulation of non-linearity effects compensation in all-optical orthogonal frequency division multiplexing systems - Azarnia, Ali (2020)
All-Optical Orthogonal Frequency Division Multiplexing (AO-OFDM) modulation technique has attracted significant attention of the optical communication community for the high speed transmission systems. This research investigates the effects of the fiber nonlinear impairments on the performance of the AO-OFDM transmission systems and proposes three AO-OFDM systems which have high tolerance against the nonlinear impairments. The first AO-OFDM system employs Differential Quadrature Phase Shift Keying (DQPSK), while the second and third systems employ m-array Quadrature Amplitude Modulation (m-QAM), and Non Return to Zero (NRZ) DQPSK, respectively. Each proposed system employs 29 subcarriers which are generated by an Optical Frequency Comb Generator (OFCG). The generated signals are transmitted over the transmission link and received by the coherent receiver. The analytical model of each system is developed to investigate the effects of various parameters such as the transmission distance, number of fiber spans, fiber dispersion, number of subcarriers, and power of subcarrier on the Nonlinear Phase Noise (NLPN) which induced by the fiber nonlinearity effects. The impacts of the NLPN due to Four-Wave Mixing (FWM), Self-Phase Modulation (SPM), and Cross-Phase Modulation (XPM) on the performance of the proposed systems are also investigated. The proposed systems are numerically simulated at the symbol rate of 25 Gsymbol/s. The optical multi-carrier signals were generated, modulated, de-correlated, and detected by the VPI transmission maker software 9.0. The received signals were linked to Matlab software and processed by using the Digital Signal Processing (DSP) algorithm in order to compensate the effects of the nonlinear impairments and improve the performance of the transmission system. The digital processing of the detected signals and Bit Error Rate (BER) calculation are performed by using DSP algorithm in Matlab software. In order to quantify the effectiveness of the proposed techniques, three AO-OFDM systems are demonstrated numerically before and after employing the nonlinearity mitigation techniques. The total phase noise variances, BER, and Error Vector Magnitude (EVM) are investigated to explore the effectiveness of the proposed technique. The results show that after using the phase noise mitigation technique, the EVM and BER are decreased by 20% and 7%, respectively. In addition, by employing the proposed technique the total phase noise variance is reduced by 50%. The simulation results clearly indicate that the constellation diagrams of the proposed system become more squeezed around the ideal constellation and the received signals are closer to the ideal point compared with the original system. That means, after employing the proposed techniques, the received signals have higher tolerance towards the fiber nonlinear impairments as compared to the original system. The obtained results show the significant improvements on the transmission performance of the proposed system after employing the post-compensation DSP or Optical Phase Conjugation (OPC) module.